STAGES OF MANAGEMENT DECISION-MAKING IN THE ESTABLISHMENT OF ENTREPRENEURIAL ACTIVITY - O‘ktamjonova , Zulayho; Nizomiddinova , Maftunaxon Shoirjonovna; Boltayeva, Ziyoda Bahodirovna (Educational Research in Universal Sciences, 2023)
This article provides information on the stages of making managerial decisions when starting a business. These decisions contain important concepts in business activities and cover many topics such as innovations, dealing with international companies, and the issue of trade protection. The article consists of five stages, including the journey of writing ideas and articles in entrepreneurial activity, business development strategy, business planning strategy, marketing strategy, choosing a strategy for working with employees and trade opponents, specializing with partners and foreign organizations, room and construction viewing and equipment organization topics are shown.